Depleting groundwater – an opportunity for flood storage?: a case study from part of the Ganges River Basin, India - Chinnasamy, Pennan (IWA Publishing, 2017)
Storing excess rainwater underground can become key in mitigating the frequency and magnitude of flood events. In this context, assessment of depleted groundwater storage that can be refilled in water surplus periods is imperative. The study uses Gravity Recovery and Climate Experiment (GRACE) data to identify variations in groundwater storage in the monsoonal Ramganga River basin (tributary of the Ganges, with an area of 32,753 km2) in India, over the nine-year period of 2002–2010. Results indicate that basin groundwater storage is depleting at the rate of 1.6 bill. m3 yr 1 . This depleted aquifer volume can be used to store floodwater effectively – up to 76% of the rainfall on average across the Ramganga with a maximum of 94% in parts of the basin. However, the major management challenge is to find and introduce technical and policy interventions to augment recharge rates to capture excess water, at required scales.